Value of various PSA parameters for diagnosing prostate cancer in men with normal digital rectal examination - Miotto Jr,Ari (2004)
OBJECTIVES: The risks of identifying prostate cancer (PCa) in patients with serum total PSA (tPSA) between 4 and 10 ng/dl are between 25 and 35%. There are no data in Brazil showing the incidence of disease when all variables for PSA assessment are considered altogether, specifically tPSA, free fraction, PSA velocity and PSA stratified by age. The objective in this work was to define the incidence of disease in a population of men with abnormal values of PSA variables and normal digital rectal examination. MATERIALS AND METHODS: Between 1998 and 2003, 273 prostate biopsies were performed by the same radiologist and analyzed by the same pathologist. All patients had a normal digital rectal examination and biopsy had been indicated due to tPSA above 4 ng/dl or free-to-total PSA ratio (F/T PSA) below 15% or PSA velocity higher than 25% per year or a PSA level regarded as high for the age range. The relationship between these parameters and the positivity for prostate caner was determined. RESULTS: Patients' mean age was 63.8 years, and PCa was identified in 135 cases (49.5%). The incidence of PCa, related to unitary variations in tPSA, ranged from the limits of 33 to 80%, respectively, in tPSA < 3 and PSA between 15.1 to 20. When the other PSA parameters were assessed (free PSA, PSA according to age, rise velocity) PCa was detected in more than 25.3% of cases. CONCLUSION: When patients with normal digital rectal examination are selected for prostate biopsy due to tPSA levels above 4 or F/T PSA ratio lower than 15% or PSA velocity higher than 25% per year or high PSA for the age range, the incidence of PCa is quite higher than that observed in a population selected exclusively with basis on total PSA value.